Covered Stent Treatment of Carotid Blowout Syndrome - Gaba, Ron C. (Thieme Medical Publishers, 2007)
Carotid artery blowout is a devastating complication of head and neck malignancy, irradiation, and trauma. New endovascular therapies of acute carotid artery rupture involve stent-directed, carotid-sparing treatment strategies. We report a case of successful covered stent treatment of carotid artery hemorrhage in the setting of head and neck cancer and review the literature describing the use of this therapeutic method. Evaluation of 19 recently reported cases of covered stent treatment of carotid artery blowout due to head and neck cancer and presenting with sentinel or acute hemorrhage demonstrates that this method is a fast and effective means of controlling bleeding, with a technical success rate of ~95%. A significant early recurrent hemorrhage rate raises concern regarding the short-term safety and efficacy of this therapy, however, and suggests that stent graft treatment of carotid artery rupture due to head and neck malignancy is best suited as a temporizing measure before more definitive therapy.